DAMPAK FINANCIAL BRAND VALUE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN (Study Perusahaan Consumer Non-Cyclicals Sub-Industri Food & Baverage 2018-2023) - Wahyuniati Hamid; Sujono; Elvi; Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Brand value is an important intangible asset that can enhance customer loyalty, reduce marketing costs, and support premium pricing, thereby contributing to a company's profitability and firm value. This study aims to examine the impact of financial brand value on profitability and firm value in the Food & Beverage sub-industry in Indonesia during the 2019–2023 period, using a quantitative research design with annual report data from 17 companies selected through purposive sampling. Data were analyzed using panel regression, classical assumption tests, and hypothesis testing. The results show that financial brand value has no significant effect, and tends to be negatively related, to ROA, ROE, and ROC. The prestige driver shows mixed and insignificant results across all three profitability indicators. The loyalty driver is the most significant positive factor influencing ROA and ROE. The extension driver generally shows no significant effect. Regarding firm value, brand value has a significant positive effect on stock price but an insignificant negative relationship with Tobin's Q. Interestingly, the previous year's brand value has a significant positive effect on ROA and ROC, indicating a long-term effect of brand value on financial performance.